A Study on Two Different Diffusion Models in a Saturated Mobile Phone Market - Xu, Li (The Graduate School, Ajou University, 2012)
The purpose of this paper is to analyze the performances of Lotka-Volterra model and extended Bass model in the saturated mobile phone communication market of Republic of Korea. The two species’ Lotka-Volterra model is tested considering competitive impact and three species’ Lotka-Volterra model is developed and applied to all the Korean mobile phone communication service providers. The performances of the Lotka-Volterra model and the extended Bass model are compared in consideration of competitive effect in the saturated market. By fitting the historical data of Korean mobile communication service market, the result shows that the goodness of fit of three species’ Lotka-Volterra model in the three companies’ competition case is better than the extended Bass model in terms of adjusted Based on the result of empirical tests, the proper advantages and disadvantages for two models are discussed.
학위논문(석사)아주대학교 국제대학원 :국제경영학과,2012. 8
Keywords: competition model; saturated market; mobile phone communication; Lotka-Volterra model; extended Bass diffusion model; Graduate school of international studies ajou university; GSIS